A model for catabolite activator protein binding to supercoiled DNA - Salemme, F. R. (1982)
Catabolite activator protein (CAP) is a dimeric molecule (M(r) = 2 × 22,500) involved in transcription initiation of several catabolite-sensitive genes of Escherichia coli. The present communication proposes a model for the interaction of CAP with DNA. The model is based upon known geometrical features of the CAP molecule [McKay, D. B. & Steitz, T. A. (1981) Nature (London) 290, 744-749], which allow interaction between dyad-related α-helices of the dimeric protein and major grooves in adjacently aligned sections of right-handed B-DNA. These geometrical features suggest that in vivo CAP binding to closed-circular DNA involves CAP bridging adjacent loops of a DNA solenoidal coil. This interaction pattern is shown to be consistent with the geometrical and stoichiometric properties of nonspecifically bound CAP complexes observed by Chang et al. [Chang, J. J., Dubochet, J., Baudras, A., Blazy, B. & Takahashi, M. (1981) J. Mol. Biol. 150, 435-439]. CAP-induced coil formation is related to in vivo CAP potentiation of RNA polymerase activity in underwound closedcircular DNA. Specifically, it is proposed that CAP binding to the right-interwound form of supercoiled DNA effects a local redistribution of DNA twist-strain energy, thus resulting in the formation of a left-handed solenoidal loop. The production of this localized solenoidal loop, which reflects compensatory alterations in DNA twist and writhe, may provide a conformationally unique site for RNA polymerase binding where the DNA is partially unwound. The proposed interaction pattern is consistent with both recent DNA unwinding experiments and various nuclease protection data. Moreover, features of the model suggest that the repetitive and symmetric character of many promoter sequences may provide the structural basis for a switching mechanism operative in the differential control of gene transcription.